Identifikasi Faktor Penyebab terjadinya Kenakalan Remaja menggunakan Metode Multi Factor Evaluation Process (MFEP) - Limbong, Riswan; Siregar, Kristian (MEANS (Media Informasi Analisa dan Sistem), 2019)
Juvenile delinquency is a very actual problem in almost every country including Indonesia. Outbreaks of cases of juvenile law violations such as robbery, robbery, fighting, theft, possession of sharp weapons and misuse of narcotics as well as various other legal violations. With so many cases of violations of the law it is illustrated that in the era of complete human development, it is expected that adolescents have the rights and obligations and responsibilities to develop the nation and state but many do unlawful acts. The Multifactor Evaluation Process (MFEP) method is a quantitative method that uses "weighting" where in multi-factor decision making, the decision maker is subjectively subjective and intuitively required to weigh various factors that have a dominant competing influence on the alternatives of their choices. Decisions that affect strategic policy, it is recommended to use quantitative approaches such as MFEP, to make an appropriate weighting must be given consideration. The same stage must also be carried out on the alternative to be chosen, which is then evaluated in relation to all factors taken into consideration and determining which alternative with the highest or maximum value is the best solution based on existing criteria.